11+3x-7=2(4x-7)+25

Simple and best practice solution for 11+3x-7=2(4x-7)+25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+3x-7=2(4x-7)+25 equation:



11+3x-7=2(4x-7)+25
We move all terms to the left:
11+3x-7-(2(4x-7)+25)=0
We add all the numbers together, and all the variables
3x-(2(4x-7)+25)+4=0
We calculate terms in parentheses: -(2(4x-7)+25), so:
2(4x-7)+25
We multiply parentheses
8x-14+25
We add all the numbers together, and all the variables
8x+11
Back to the equation:
-(8x+11)
We get rid of parentheses
3x-8x-11+4=0
We add all the numbers together, and all the variables
-5x-7=0
We move all terms containing x to the left, all other terms to the right
-5x=7
x=7/-5
x=-1+2/5

See similar equations:

| 285−5x=340−10x | | 3w-9=6w | | 2x+34+8=x+30 | | 9m+16=2m-19 | | x-2=7x+7+2x | | 3m-5=6m=-5 | | 6r+7-7r=13 | | 25+f=47 | | x+49=109 | | 0.4x2.8/4=1.5 | | (h)/(8)=-4 | | 11h-(2h-1)=18 | | n/13(2n−5)=7 | | 13x+10=8x+8+4x+14 | | 8x+25=64+5x | | 3x-4=-1x+2 | | -3(2x-1)+4x=17 | | 4(x+8)=3(x–6) | | 0.05(3x-2)=0.35 | | 12x2+16x+1=0 | | x*5.4=11.5 | | 6x+1=2x-7+4x | | 3x-4=5+6x | | (12x+25)/13=13 | | -6x+20=10x-16 | | 48=2x+6= | | x/48=0 | | 2g-21=1 | | (10x-7)(4x+6)=5x | | 3x+12-4x=23 | | 10x-69=12x-25 | | x~5.4=11.5 |

Equations solver categories